Production of polyhydroxybutyrate in oil palm (Elaeis guineensis Jacq.) mediated by microprojectile bombardment of PHB biosynthesis genes into embryogenic calli - Parveez, Ghulam Kadir Ahmad; Bahariah, Bohari; Ayub, Nor Hanin; Masani, Mat Yunus Abdul; Rasid, Omar Abdul; Tarmizi, Ahmad Hashim; Ishak, Zamzuri (Frontiers in Plant Science, 2015)
Biodegradable plastics, mainly polyhydroxybutyrate (PHB), which are traditionally produced by bacterial cells, have been produced in the cells of more than 15 plant species. Since the production of biodegradable plastics and the synthesis of oil in plants share the same substrate, acetyl-coenzyme A (acetyl-CoA), producing PHB in oil bearing crops, such as oil palm, will be advantageous. In this study, three bacterial genes, bktB, phaB and phaC, which are required for the synthesis of PHB and selectable marker gene, bar, for herbicide Basta resistant, were transformed into embryogenic calli. A number of transformed embryogenic lines resistant to herbicide Basta were obtained and were later regenerated to produce few hundred plantlets. Molecular analyses, including PCR, Southern blot and real-time PCR have demonstrated stable integration and expression of the transgenes in the oil palm genome. HPLC and Nile Blue A staining analyses confirmed the synthesis of PHB in some of the plantlets.